Meningkatkan Motivasi Belajar Pada Peserta Didik Kelas VII A SMP Xaverius Metro Materi Yesus Sang Pengampun Dengan Metode Diskusi dan Presentasi - Endi Priyanto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The problem in this research is whether discussion and presentation methods can increase learning motivation in class VIIA students at Xaverius Metro Middle School. The research method used was the classroom action research (PTK) method which was carried out at Xaverius Metro Middle School on Class VIIA students totaling 28 students. This research was carried out over two actions (cycles). Data collection techniques through observation, questionnaires and learning outcomes tests. The research results showed that there was an increase in motivation, attitudes and learning outcomes through the use of group discussion and presentation methods for class VIIA SMP Xaverius Metro. The increase in this research is quite significant, namely that the independence of students who are developing has decreased from 1 student (3.57%) in cycle I, and to 0 students (0%) in cycle II. The qualification that stated students were quite independent decreased from 12 students (42.86%) in cycle I, and to 10 students (35.71%) in cycle II. The qualifications that stated independent students decreased from 12 students (42.86%) in cycle I, and to 11 students (39.29%) in cycle II. The qualification that states students are very independent has increased from 3 students (10.71%) in cycle I, and to 7 students (25.00%) in cycle II. Students' attitudes increased significantly from 5 students (17.86%) in cycle I, and to 6 students (21.43%) in cycle II. Qualifications that stated they were good decreased from 23 students (82.14%) in cycle I, and to 16 students (57.14%) in cycle II. The qualifications that stated they were very happy had increased from 0 students (0%) in cycle I, and to 7 students (25.00%) in cycle II. The results of the student learning evaluation showed that it was developing, experiencing a decrease from 3 students (10.71%) in cycle I, and to 0 students (0%) in cycle II. The qualifications that stated they were worthy decreased from 10 students (35.71%) in cycle I, and to 4 students (14.29%) in cycle II. Qualifications stating that they were proficient increased from 7 students (25.00%) in cycle I, and to 9 students (32.14%) in cycle II. The qualifications for proficient increased from 8 students (28.57%) in cycle I, and to 15 students (53.57%) in cycle II. This means that the results obtained have met the criteria for completing the lesson objectives (KKTP).